Answer:
In order that both functions to represents the same (one) graph then the value of k is 5
Explanation:
The given functions are;
f(x) = 6·x² - 12·x + 11
g(x) = 6·(x - 1)² + k
Expanding the function g(x) gives;
6·(x - 1)² + k = 6 × (x² - 2·x + 1) + k = 6·x² - 12·x + 6 + k
∴ 6·(x - 1)² + k = 6·x² - 12·x + 6 + k
Comparing with the function for f(x), we have;
f(x) = 6·x² - 12·x + 11
g(x) = 6·(x - 1)² + k = 6·x² - 12·x + 6 + k
The difference between the two functions is the constant term, which are;
Constant term for f(x) = 11
Constant term for g(x) = 6 + k
For the two terms to describe exactly the same graph, the constant term should also be equal
We will then have, 11 = 6 + k
∴ k = 11 - 6 = 5
k = 5
For both functions to represent the same graph the value of k = 5.